Study of effect of maternal nutrition on breast milk trace elements in malnourished versus well-nourished mothers - Mane, Sharmila M.; Patil, Neelam J.; Nerurkar, Alka V. (International Journal of Advances in Medicine, 2018)
Background: Minerals and trace element content of human milk have been a matter of concern among nutritionist in relation to the availability of the essential elements to the new born. Mineral and trace elements occur in the body in a number of chemical forms, such as inorganic ions and salts, or as constituents of organic molecules, for example proteins, fats, carbohydrates and nucleic acids. There is a paucity of data on the effect of nutrition on the composition of trace elements in milk and its effect on the infant. Hence a comparison made between the trace element and mineral such as sodium, potassium, magnesium, iron, zinc, copper, calcium in milk of malnourished and well-nourished mothers in order to determine the effect of maternal nutrition on the quality of milk and its effect on the growth and physical development of the new-born. Methods: Around 100 mothers were enrolled in the study after obtaining prior informed consent. They were divided into 2 groups-group I had 50 malnourished mothers and group II had 50 well-nourished mothers. The pre-fed milk sample which was collected was stored at - 20℃ until it was processed. It was thawed and analysed for copper, zinc, iron, magnesium, sodium, potassium and calcium. Results: The mean levels of trace elements (iron and zinc) and minerals (sodium, potassium, calcium, magnesium) were slightly more among well-nourished than malnourished women. Values of only copper were significantly higher in the colostrum of well-nourished as compared to that of the malnourished mothers. Conclusions: The parameters of weight, height weight/height ratio and hemoglobin varied significantly between the well-nourished and malnourished mothers. The difference in milk content of malnourished and well-nourished mothers is not significant for sodium, potassium, calcium, iron, magnesium, zinc. However, copper levels were significantly higher in well-nourished mothers.